Activation of central/effector memory T cells and T‐helper 1 polarization in malignant melanoma patients treated with anti‐programmed death‐1 antibody. Issue 10 (31st August 2018) - Yamaguchi, Kyoko; Mishima, Koji; Ohmura, Hirofumi; Hanamura, Fumiyasu; Ito, Mamoru; Nakano, Michitaka; Tsuchihashi, Kenji; Ota, Shun‐Ichiro; Wada, Naoko; Uchi, Hiroshi; Ariyama, Hiroshi; Kusaba, Hitoshi; et al.
Abstract : Human anti‐programmed death‐1 (PD‐1) antibody possesses the capability to revitalize host T cells and has been an effective therapy for metastatic malignant melanoma (MM). The precise subsets of T cells predominantly activated by anti‐PD‐1, however, have not yet been clarified. In this study, peripheral blood mononuclear cells obtained from MM patients scheduled to receive anti‐PD‐1 (nivolumab) therapy, and healthy subjects (HS), were systematically examined on flow cytometry to identify changes in the proportion of immune cell subsets. Compared with HS, MM patients prior to therapy had an increased proportion of activated CD8+ T cells with effector memory phenotypes (Tem), and PD‐1 positive subsets of CD4+ central memory T cells (Tcm) and T‐helper (Th)17 cells. After a single course of anti‐PD‐1 therapy, MM patients had an increase in activated Tem and Tcm subsets of CD4+ and CD8+ T cells, and activated Th1 plus T‐helper follicular 1 cells. There was no consistent change in the proportion of Tfh cells, B cells, natural killer cells, or dendritic cells. The observed activated phenotypes were attenuated during the course of therapy, but regulatory T cells belonging to the CD3+CD4+CD45RO+CD25high fraction increased at disease progression. Taken together, anti‐PD‐1 therapy modulates systemic immune reactions and exerts anti‐tumor effects, not only by revitalizing Tem and Tcm of CD4+ and CD8+ T cells, but also via a shift to a Th1 phenotype. Abstract : On comprehensive analysis of peripheral blood immune cells in malignant melanoma (MM) patients treated with anti‐programmed death‐1 (PD‐1)‐1 antibody, the therapy modulated systemic immune reaction and exerted anti‐tumor effect, not only by selective activation of the PD‐1 signaling of central memory and effector memory T cells (Tcm/Tem), but also via a shift to a T‐helper 1 (Th1) phenotype. Gradual attenuation of these effects with time suggested a homeostatic system to balance PD‐1 blockade.